The Economic And Social Approach Of Government Subsidy Policy In Algeria - Dallaa, Dalila; Belhaoues ,Salima (جامعة الوادي University of Eloued, 2024)
This researchThis research paper aims to evaluate and diagnose the government subsidy policy through an economic-social approach in Algeria, in order to highlight the extent to which it is able to respond to the criteria of economic efficiency on the one hand and achieve societal justice on the other, through this study, we have addressed the concept of government subsidies the we tried to assess the economic and social effects of this policy. The study concluded that the government subsidy policy in Algeria was able to achieve its desired goals, but it was not subject to the criteria of economic efficiently and social justice.
Keywords: Government subsidies; Socio-economic approach; Economic efficiency; Social justice; Algeria